Experiências em ações promocionais mediadas tecnologicamente - Jurado, Maria Antonia Rivera (2016)
This research proposes a look at the experiences with interactive media and the current implementation of its poetic potential in brand promotional activities, whose combination of languages and resources from multiple disciplines, is setting new transmedia products and communicative models, with a growing presence in the contemporary market. Methodologically, after establishing a theoretical basis of the disciplines involved in the creation and diffusion of this advertising experiences, this qualitative research was based on the observation and semiotic analysis of the poetic strategies present in some of them, according to their ability to provide a closer relationship between their consumers and the brand values that these promote. Later, as a practical application of the information / observations gathered, went up to the Promotional Project Pyxis design - P³: an advertising action boosted by an interactive experience of virtual reality, focused on disclosure and positioning of the Media Lab / UFG brand. From this process we discuss the concepts referenced throughout the research, to finally point out some of the implications and dynamics that these new media products bring to the experiences with brands, design of interactive experiences and the current advertising communication.